Psychological perspectives on ethical behavior and decision making - De Cremer, David (Emerald Publishing Limited : Information Age Publishing, 2009)
The book is divided into three relatively coherent sections that focus on understanding the emergence of (un)ethical decisions and behaviors in our work and social lives by adopting a psychological framework. The first section focuses on reviewing our knowledge with respect to the specific notions of ethical behavior and corruption. These chapters aim to provide definitions, boundary conditions and suggestions for future research on these notions.The second section focuses on the intra-individual processes (affect, cognition and motivation) that determine why and how people display unethical behavior and are able to justify this kind of behavior to a certain extent. In these chapters the common theme is that given specific circumstances psychological processes are activated that bias perceptions of ethical behavior and decision making.The third section explores how organizational features frame the organizational setting and climate. These chapters focus on how employment of sanctions, procedurally fair leadership and a general code of conduct shapes perceptions of the organizational climate in ways that it becomes clear to organizational members how just, moral and retributive the organization will be in case of unethical behavior.